Primary Lymphoepithelioma-Like Carcinoma of the Conjunctiva Metastatic to Regional Lymph Nodes and Parotid Gland in a Mexican Patient - Ana Lía Díazceballos-García; Sebastian Diener-Kudisch; Abelardo A. Rodriguez Reyes; Ángel Nava-Castañeda (Case Reports in Ophthalmological Medicine)
Lymphoepithelioma-like carcinoma (LELC) of the conjunctiva is a rare malignancy in the ocular adnexa. There are no prospective data regarding treatment methods. Complete surgical excision is sufficient in the majority of cases. Radiation therapy is sometimes used in case of recurrence or positive margins after surgery. This case describes an 89-year-old Hispanic female with a 7-month history tumor primarily located on the left lower palpebral conjunctiva. The patient underwent an excisional biopsy of the tumor, and histopathology exam reported an LELC with positive margins. She developed parotid and neck lymph node metastasis treated with concurrent radiotherapy. The patient had remained disease-free for 3 years. According to the available data, there are only five cases of LELC reported in conjunctiva worldwide, so this report increases the differential diagnoses of tumors in the ocular adnexa and supports the effectiveness of radiotherapy.